Regional flow frequency analysis on Peninsular Malaysia using L-moments / Aminuddin Mohd Baki ... [et al.] - Mohd Baki, Aminuddin; Mat Yusof, Doris Asmani; Atan, Ismail; Mohd Halim, Nora Farina (Universiti Teknologi MARA, Perlis, 2015)
Through this study, regional estimation has been proposed as an alternative technique to estimate design runoff. Regional frequency analysis of annual runoff in Peninsular Malaysia has been conducted and was based on the theory of L-Moments as developed by Hosking and Wallis (1997) is a very reliable method for assessing exceedance probabilities of extreme environmental events when data is available from more than one site. This recommended technique will definitely enhance the accuracy of the design runoff and at the same time will minimize the uncertainties of observed data. The objectives of this study are to identify the homogeneous region and to establish the best fitted distribution for each region. The study area was separated into five homogeneous regions. The General Logistics (GLO) was found to be the best distribution for the region in peninsular Malaysia followed by Generalized Extreme Value (GEV). The best fit distributions of annual runoff in Malaysia are discovered based on L-moment ratio diagram and statistical tests. Numerical analysis was carried out on some stations in every state in Peninsular Malaysia. Thus, the analysis performed are using data from homogeneous regions determine using L-moments process. The Frequency analysis using a regional approach based on L-moments method was detected to be practical in the estimation of design runoff at ungauged site.